English law in the age of the Black Death, 1348-1381 : a transformation of governance and law - Palmer, Robert C., 1947- (The University of North Carolina Press, 1993)
Robert Palmer's pathbreaking study shows how the Black Death triggered massive changes in both governance and law in fourteenth-century England, establishing the mechanisms by which the law adapted to social needs for centuries thereafter. Palmer is the first scholar to relate these medieval legal changes to social and demographic developments. The Black Death killed one-third of the English population between 1348 and 1351. To preserve traditional society, the king's government aggressively implemented new punitive legal remedies as mechanisms for social control. The changes inaugurated included Statute of Laborers prosecutions, penal bonds, uses, trespass on the case, and assumpsit. The government's attempt to shore up traditional society in fact transformed it. English governance was legitimately extended to routine regulation of all workers, from shepherds to innkeepers, smiths, and doctors. The new cohesiveness of the ecclesiastical and lay upper orders, the increase in subject matter jurisdictions, the growth of the chancellor's court, and the acceptance of coercive contractual remedies made the Black Death in England a transformative experience for law and for governance. Based on all available legal records, Palmer's book presents a new interpretation and chronology of these important legal changes and also establishes a policy foundation. The footnotes and appendixes present additional information on church-state relations and on the history of various occupations.
Keywords: Law -- England -- History.; Great Britain -- Politics and government -- 1327-1377.; Black Death -- Social aspects -- England -- History.; England -- Social conditions -- 1066-1485.; Law, Medieval.; Great Britain -- Politics and government -- 1066-1485.; Grande-Bretagne -- Politique et gouvernement -- 1066-1485.; Droit -- Angleterre -- Histoire.; Grande-Bretagne -- Politique et gouvernement -- 1327-1377.; Peste noire -- Aspect social -- Angleterre -- Histoire.; Angleterre -- Conditions sociales -- 1066-1485.; Droit médiéval.; LAW -- Administrative Law & Regulatory Practice.; Black death -- Social aspects; Law; Law, Medieval; Politics and government; Social conditions; England; Great Britain; Rechtshervorming.; Common law.; Pest (ziekte); Droit -- Angleterre (GB) -- Histoire -- 14e siècle.; Peste -- Aspect social -- Angleterre (GB); Social Conditions -- history; Plague -- history; Legislation as Topic -- history; Law.; Law -- Great Britain -- History.; Social history -- Great Britain -- Medieval period, 1066-1485.; Black Death -- Social aspects -- Great Britain -- History.; 1066-1485; Black Death -- Social aspects -- History -- England; England -- Social conditions -- 1066-1485; Geschichte -- 1348-1381; Great Britain -- Politics and government -- 1327-1377; Law -- History -- England; History